Translucency and color stability of resin composite and dental adhesives as modeling liquids - A one-year evaluation - José Augusto SEDREZ-PORTO; Eliseu Aldrighi MÜNCHOW; Maximiliano Sérgio CENCI; Tatiana PEREIRA-CENCI (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract The aim of this study is to evaluate the influence of modeling liquids on the translucency and color shade of resin composites (RCs) after one year of storage. RC specimens were prepared using either a conventional insertion technique (control; without modeling liquid) or a restorative dental modeling insertion technique (RDMIT) with dental adhesives as modeling liquids (Scotchbond™ Multi-Purpose [SBMP; 3M ESPE] or Adper™ Single Bond 2 [SB; 3M ESPE]). The initial colors of the specimens were obtained with a digital spectrophotometer and the CIEL*a*b* color system, after which specimens were stored (37°C) in distilled water or red wine for 12 months. Color measurements were reassessed after 6 and 12 months of storage, and scanning electron microscopy was performed after 12 months. Translucency and color change (ΔE*) were calculated and analyzed using ANOVA and Tukey's test (α = 5%). RC samples prepared via RDMIT showed a translucency similar to that of control samples. ΔE* was also less intense for RCs containing SBMP than for RCs containing SB. Specimens stored in wine showed a clear pattern of degradation, especially in the control group, and surface degradation seemed to be less intense for specimens prepared with SBMP and SB than for specimens without. Specimens stored in water did not show clear evidence of surface degradation. RDMIT appears to be an interesting approach to reduce ΔE* in RCs over time without negative effects on the translucency of the material. However, the modeling liquid should feature a hydrophobic composition, similar to that used in the SBMP group, the achieve the best results.